Cocaine and MDMA Induce Cellular and Molecular Changes in Adult Neurogenic Systems: Functional Implications - Vivian Capilla-Gonzalez; Vicente Hernandez-Rabaza (MDPI AG, 2011)
The capacity of the brain to generate new adult neurons is a recent discovery that challenges the old theory of an immutable adult brain. A new and fascinating field of research now focuses on this regenerative process. The two brain systems that constantly produce new adult neurons, known as the adult neurogenic systems, are the dentate gyrus (DG) of the hippocampus and the lateral ventricules/olfactory bulb system. Both systems are involved in memory and learning processes. Different drugs of abuse, such as cocaine and MDMA, have been shown to produce cellular and molecular changes that affect adult neurogenesis. This review summarizes the effects that these drugs have on the adult neurogenic systems. The functional relevance of adult neurogenesis is obscured by the functions of the systems that integrate adult neurons. Therefore, we explore the effects that cocaine and MDMA produce not only on adult neurogenesis, but also on the DG and olfactory bulbs. Finally, we discuss the possible role of new adult neurons in cocaine- and MDMA-induced impairments. We conclude that, although harmful drug effects are produced at multiple physiological and anatomical levels, the specific consequences of reduced hippocampus neurogenesis are unclear and require further exploration.